Mathematical Critical Thinking Abilities of Students in Terms of Self-Regulated Learning in Realistic Mathematics Education Assisted By Mobile Learning - Nashrullah, Fahmi Rizqi; Rochmad, Rochmad; Cahyono, Adi Nur (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The students' mathematical critical thinking ability is categorized as still not good due to the teaching and lack of use of instructional media in the learning process. These factors also contribute to the students' low level of learning independence. Several studies have found that the mathematical critical thinking ability is still below average. One of the teaching methods that can help improve students' mathematical critical thinking ability is Realistic Mathematics Education (RME) assisted by mobile learning. This study aims to: (1) Test the effectiveness of RME assisted by mobile learning on students' mathematical critical thinking ability, and (2) Analyze and understand students' mathematical thinking ability in terms of their learning independence in RME assisted by mobile learning. The research method used is a mixed method with concurrent embedded research design. Quantitative research serves as the primary method, and qualitative research as the secondary method. The population in this study consists of seventh-grade students at MTs Al Wahdah Sumber in the academic year 2022/2023. The sample is determined using purposive sampling technique, selecting two classes as samples - Class VII A as the control group and Class VII B as the experimental group. Data collection techniques used in this study include tests, questionnaires, documentation, and interviews. Data analysis includes individual mastery test, classical mastery test, mean difference test, and proportion difference test. The results of this study indicate that: (1) RME assisted by mobile learning is effective in improving students' mathematical critical thinking ability, as evidenced by the average mathematical critical thinking ability of the experimental group reaching the actual mastery level, 75% mastery proportion in the experimental group, higher mean difference in the experimental group compared to the control group, and higher proportion in the experimental group compared to the control group, and (2) Diverse mathematical critical thinking abilities were found in the low, medium, and high learning independence groups.